Experience of Top Performers in the Health Sciences Licensure Examination in a Selected University - Pena, Lucinda Dela; Escasa, Ronald Jay; Labro, John Jerico; Samson, Mark B. (11th International Scholars Conference, 2018)
The quality of education offered by an institution is often determined by the graduates it produces; likewise, the quality of graduates produced by an institution is measured by their performance in the licensure examinations. This study attempted to capture the lived experiences of the top performers in the different health sciences licensure examinations in a selected university. Descriptive phenomenological method was used to extract information on the experiences of the eight top performers from the four departments: Nursing, Medical Technology, Psychology, and Dentistry who graduated from a selected university in Silang, and are currently working in the Philippines. A formulated set of questions served as the primary method for data collection. Triangulation of the data utilizing interviews with their deans and instructors was used and thematic analysis was done using Collaizi’s method. Three emergent themes encapsulated the experiences of the informants before, during and after the licensure exam. First is their preparation, with four occurring facets: academic, spiritual, psychosocial, and physical. The next theme is anxiety, wherein all of the eight informants claimed the notion of inadequacy of knowledge and possibility of failing. The last theme is the impact of the licensure exam success in the lives of the top performers, with three commonalities among them: strengthened faith, increased opportunity, and widened influence. It was evident that a holistic approach was seen in the preparation of the informants and despite the anxiety, they were able to perform satisfactorily which brought them advances in their professional career and spiritual life. Holistic approach should be considered in designing learning plans to produce high-performing graduates.